Pregnancy outcome in women with subchorionic haemorrhage detected in first and second trimester of pregnancy - Retha, Parez; Shekh Mohammed, Samira S.; Hassen, Parween Omer (Zanco Journal of Medical Sciences (ZJMS), 2015)
Background and objective: Subchorionic hemorrhage is the most common sonographic abnormalities and the most common cause of first trimester miscarriage and mainly associated with vaginal bleeding. The present study was conducted with an aim to find out the effect of subchorionic hemorrhage in first and second trimester of pregnancy outcome. Methods: A case cohort prospective study was designed to investigate 100 patients having a subchorionic hematoma in the presence of singleton live embryo or fetus. The study assessed the association of the volume size of subchorionic hematoma, maternal age and gestational age at time of the diagnosis with adverse pregnancy outcomes. Results: The incidence of miscarriage and preterm delivery was 35% and 21% respectively. The mean (±SD) age of those who aborted was 29.97 ± 7.0 years, slightly higher than the mean age of those who ended with preterm delivery (27.7 ± 5.87 years) and those continued with their pregnancies to viability (28.3 ± 6.2 years). There was a statistically significant association between previous histories of preterm delivery and pregnancy outcome (P =0.015). Miscarriage was significantly high among women with gestational age <12 weeks, while term pregnancy was significantly high among women with gestational age >13 weeks (P <0.001). The estimated volume of the hematoma did not correlate with the outcome of the pregnancy, perhaps it is the presence or absence of a hematoma as a marker of the integrity of placentation and not its size. Conclusion: Subchorionic hematoma in first and second trimester of pregnancy associated with adverse pregnancy outcome (spontaneous miscarriage and preterm delivery.